‘I am the master key that opens and locks’: Presentation and application of a conceptual framework for women's and girls' empowerment in reproductive health - Karp, Celia; Wood, Shannon N.; Galadanc, Hadiza (Elsevier, 2020)
ationale: A renewed focus on women's and girls' empowerment in the era of Sustainable Development Goals reflects the belief that empowerment is central to health and development. Sexual and reproductive health (SRH) outcomes, including pregnancy and contraceptive use, may contribute to and result from empowerment. However, enhanced understanding of how women become empowered for SRH requires clear conceptualization of empowerment. Objective: We aimed to assess the applicability of a proposed framework for women's and girls' SRH empowerment (WGE-SRH) in sub-Saharan Africa. We sought to understand what shapes and motivates preferences for childbearing and contraception, exploring how women and girls navigate external pressures or rewards to exercise and achieve their reproductive goals. Methods: Grounded in the WGE-SRH framework, we conducted a qualitative study in four distinct contexts (Ethiopia, Kano and Anambra States in Nigeria, and Uganda). We implemented and analyzed 120 in-depth interviews and 38 focus group discussions with 440 women and men and translated results to refine the WGE-SRH framework. Results: Findings demonstrate the salience of women's internal motivations, including the social value and joys of motherhood, in shaping existence of reproductive choices. However, existence of choice was limited by couples' economic situations, pressures from providers, partners, and family members, and women's fears of contraceptive side effects or relationship dis- solution. Despite these constraints, many found ways to exercise their reproductive choices through negotiation with partners, third party involvement in reproductive discussions, non-verbal communication, and covert use of contraception. Conclusions: The WGE-SRH framework is useful for exploring SRH empowerment, embracing the multilevel, dynamic nature of empowerment, as a process transitioning from existence of choice (autonomy) to exercise of choice (self-efficacy, decision-making, negotiation), and, ultimately, to achievement of choice. Future research and programs related to SRH empowerment should distinguish between existence and exercise of choices to promote the health and well-being of women and girls.
Keywords: Empowerment; Reproductive health; Fertility; Family planning; Qualitative research; Community norms; Women's health; Sub-Saharan Africa; Simon Peter Sebina Kibira; Fredrick Makumbi; Bayero University, Kano; ACEPHAP; ACE: Population Health and Policy